Interview: Nanomedicine: past, present and future. (April 2013) - Webster, Thomas J
Professor Thomas Webster received his Bachelor of Science degree in chemical engineering from the University of Pittsburgh (PA, USA) in 1995. He subsequently received his Masters degree in biomedical engineering in 1997 from Rensselaer Polytechnic Institute (NY, USA). He completed his PhD at the same institution in 2000. Currently, Professor Webster is the Department Chair and Professor of Chemical Engineering at Northeastern University (MA, USA). He previously held the position of Associate Professor for the Division of Engineering at Brown University (RI, USA) and the Division of Orthopedic Surgery at Brown University Medical School. He is an elected Fellow of the American Institute for Medical and Biological Engineering, which represents the top 2% of all medical and biological engineers. Professor Webster's research has led to the formation of nine start-up companies. He has authored over 400 peer-reviewed publications and issued more than 30 patents.